Can intensity in strength training change caloric expenditure? Systematic review and meta‐analysis. (22nd November 2019) - João, Gustavo Allegretti; Rodriguez, Daniel; Tavares, Lucas D.; Carvas Junior, Nelson; Miranda, Maria Luiza; Reis, Victor M.; Bocalini, Danilo Sales; Baker, Julien S.; Figueira, Aylton J.
Summary: Introduction: Strength training (ST) is considered an important strategy for maintaining body weight, as it promotes an increase in total energy expenditure (EE). However, the combination and manipulation of variables (intensity and volume) allow for different training adaptations. However, it remains unclear as to what is the most important variable between volume or intensity for example number of sets, repetitions, or total load for maximizing EE during ST. Several studies have analyzed the EE response in ST, but still unclear the variable is able to increase EE in the ST. Objective: This review aimed to investigate the effect of ST on EE in adults using a systematic literature review and subsequent meta‐analysis. Methods: The search was performed on the electronic databases using the following keywords: strength training (resistance training; strength training; strength training method) and energy expenditure (energy metabolism; energy expenditure; caloric expenditure, caloric cost) with 'AND' and 'OR' combination. Manual searches of references were also conducted for additional relevant studies. After evaluating the inclusion and exclusion criteria, the selected studies were analysed according to strength training methods and the training variables used to measure EE. Results: We identified two ST methods from the literature review: circuit training (CT) and traditional training (TT). Meta‐analysis showed a significant effect on EE increase, which favour TT when compared with CT [−0·99 (95%CI: −1·96, −0·02), P <0·01] with I 2 of 89% ( P <0·01). After adjusting for bias risk, no significant differences were found in EE associated with intensity [−0·40, 95% CI (0·98, 0·18), P = 0·18). Conclusion: The present review and meta‐analysis indicated that the intensity of exercise does not seem to be associated with an increase of EE in ST.